Islamic Islamic Educational Thought in the Contemporary Era According to K.H. Ahmad Mustofa Bisri (Gus Mus) - Iffa Hulawalia; Mahariani; Muh. Khaidir Nahsyam; Nur Rahmah Al Haqq; Ahmad Hariyadi (IKIP PGRI Bojonegoro, 2025)
This article examines the thoughts of KH. Ahmad Mustofa Bisri (Gus Mus) on Islamic education in the contemporary era, emphasizing the importance of the process of humanizing individuals, shaping socially devout beings, and fostering self and environmental reflection. The background of this study stems from concerns over educational practices increasingly trapped in formality and material achievement orientation, thereby neglecting humanitarian values and spirituality. The aim of this study is to explore the humanistic Islamic educational ideas proposed by Gus Mus as a response to the challenges of the times. This research employs a qualitative method using a literature study approach, analyzing Gus Mus's sermons and poems rich in moral and educational messages. The findings indicate that Gus Mus stresses the importance of education not merely as a means of producing intelligent individuals, but more crucially, as a means of shaping humans with social sensitivity, self-awareness, and spiritual depth. According to him, Islamic education should serve as a medium for